Graphene oxide, GO, as immunostimulator in controlling Motile Aeromonad Septicemia (MAS) due to Aeromonas hydrophila in red hybrid tilapia, Oreochromis sp. farming - Lee Seong Wei; An'amt, M.N.; Wendy Wee; Zulhisyam Abdul Kari @ Abdullah; Hasnita Che Harun (International Science Community Association, 2016)
In the present study, the potential of graphene oxide, GO, was evaluated as immunostimulator in controlling Motile Aeromonad Septicemia (MAS)due to Aeromonas hydrophila infected in Red Hybrid Tilapia. MAS due to A. hydrophila was recognized as main constraint in red hybrid tilapia farming and may lead to mass mortality of the infected fish either marketable size or fish fry. Many of commercial antibiotics were found no longer effective to control this bacterial disease. The fish farmers were left with no option and have to continue use the antibiotics in order to overcome this disease. Therefore, this study was conducted to investigate the potential of GO to control this bacterial disease problem. In the present study, minimum inhibitory concentration (MIC) of GO extract against A. hydrophila was determined via two fold microbroth dilution method. The effectiveness of GO as an immunostimulator agent was evaluated. The experimental fish were fed with medicated feed at three different concentrations (25 mg kg-1; GO-25, 50 mgkg-1; GO-50 and100 mgkg-1of fish; GO-100) of GO for one week before they were intraperitoneally exposed to A. hydrophila. Enzyme linked immunosorbent assay (ELISA) was carried out to determine the value of antibody response to A. hydrophila in fish from group of fish that received medicated fish and the percentage of total cumulative mortality of the experimental fish were observed at the end of the experiment. The results of the present study showed the value of antibody response to A. hydrophila in fish from group of fish which received medicated feed (GO-25, 0.138 0.012 OD; GO-50, 0.112 0.013 OD; GO-100, 0.141 0.12 OD) were found significantly higher (P< 0.05) compared to fish did not received medicated fish (0.00 OD). Whereas, percentage cumulative mortality of fish from all groups of fish received medicated feed (GO-25, 22.0 1.1 %; GO-50, 23.2 1.8 %; GO-100, 21.7 1.3 %) were found significantly lower (P< 0.05) compared to group of fish did not received medicated feed (70.2 3.2 %). The findings of the present study indicated the huge potential of GO to replace commercial antibiotic as immunostimulator agent for aquaculture uses.